(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article delves into the essential aspects of designing clothing for pregnant women, offering preliminary insights into the unique considerations involved. It explores the development of constructions tailored to meet the specific needs of expectant mothers, emphasizing the imperative of creating comfortable and hygienic garments within production settings. The article underscores the significance of enhancing the design system for maternity clothing and advocates for increased public awareness of the challenges faced by pregnant women in finding suitable attire. Through a comprehensive study, the article highlights the importance of producing high-quality and competitive garments that cater to the specific demands of this demographic, aiming to contribute to a more inclusive and supportive fashion industry."